Environmental factors influencing participation of stroke survivors in a Western Cape setting - Cawood, Judy (Afr J Disabil, 2015)
BACKGROUND: Environmental factors compound or diminish the effects of impairments; therefore they have a direct influence on participation of stroke survivors. OBJECTIVES: To determine environmental barriers and facilitators to participation experienced by a group of stroke survivors in the Western Cape province of South Africa. METHODS: A descriptive, mixed methods study was conducted in 2011. Quantitative data was collected with the International Classification for Functioning, Disability and Health core set for stroke (environmental factors), from 53 stroke survivors, sampled through proportional, stratified, random sampling. Data is presented through graphs and tables. Qualitative data was collected from five purposively sampled participants and thematically analysed. RESULTS: Under products and technology, participants regarded assets, food, products and technology for daily living, transportation, mobility and communication, and access to buildings as barriers. The physical geography and attitudes of friends and society created further barriers. With regard to services, systems and policies - housing, communication, transport and social services created barriers. Health services, as well as support from health care service providers and family were considered facilitators. CONCLUSION: A lack of assets compounded barriers with regard to food, products for daily use, communication and transport. Barriers to participation were exacerbated by a lack of services, systems and implementation of policies focused on the inclusion of people with disabilities, as well as minimal access to assistive devices. Recommendations include provision of assistive devices, structural changes to houses, yards, roads and buildings, lobbying for accessible, affordable public transport, access audits of public buildings, and inclusion of non-governmental organisations and home-based care services in a seamless network of care.